2020
DOI: 10.1097/mph.0000000000001959
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life for Children With Leukemia: Child and Parental Perceptions

Abstract: Background: The importance of health-related quality of life (HRQoL) in patients with acute lymphoblastic leukemia (ALL) has increased in recent years. This study aimed to assess HRQoL in children with ALL, affecting factors, and the relationship between parent proxy-report and child self-report HRQoL. Materials and Methods: A total of 59 children and their parents (both mother and father) were enrolled in this cross-sectional study. Turkish version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…The reasons for this could be several. First, parents with high levels of distress or low HRQoL themselves tend to rate their child's HRQoL as low, 7,18,57–61 and parents, especially mothers, of children recently treated for cancer have been shown to have impaired HRQoL, 59,62 which is true also for this cohort 45 . Second, after a life‐altering event such as being diagnosed with a life‐threatening disease, a phenomenon referred to as response shift often occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this could be several. First, parents with high levels of distress or low HRQoL themselves tend to rate their child's HRQoL as low, 7,18,57–61 and parents, especially mothers, of children recently treated for cancer have been shown to have impaired HRQoL, 59,62 which is true also for this cohort 45 . Second, after a life‐altering event such as being diagnosed with a life‐threatening disease, a phenomenon referred to as response shift often occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Una enfermedad catastrófica como el cáncer genera repercusiones a corto, mediano o largo plazo tanto en el enfermo como en su familia. La importancia radica en el rol fundamental que cumple la salud mental como coadyuvante de la salud física y en las consecuencias emocionales, sociales y de conducta que pueden generarse tras el diagnóstico de una enfermedad con una alta morbimortalidad (4).…”
Section: Introductionunclassified
“…Other studies have found no age effect (Rosenberg et al, 2016). Additionally, family factors, such as lower household income (Ilowite et al, 2018; Robson et al, 2021), greater family psychosocial risk (Pierce et al, 2017), maternal chronic disease (Ocak et al, 2021), family conflict (Desjardins et al, 2022), and unhealthy family functioning (Zheng et al, 2018) are also associated with lower quality of life in children with cancer.…”
Section: Introductionmentioning
confidence: 99%